2012
DOI: 10.1364/oe.20.00a366
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming the black body limit in plasmonic and graphene near-field thermophotovoltaic systems

Abstract: Near-field thermophotovoltaic (TPV) systems with carefully tailored emitter-PV properties show large promise for a new temperature range (600 – 1200K) solid state energy conversion, where conventional thermoelectric (TE) devices cannot operate due to high temperatures and far-field TPV schemes suffer from low efficiency and power density. We present a detailed theoretical study of several different implementations of thermal emitters using plasmonic materials and graphene. We find that optimal improvements ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
188
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 209 publications
(188 citation statements)
references
References 49 publications
0
188
0
Order By: Relevance
“…Optimization of TPV efficiency in NF however is difficult due to proximity effects [20]. Thus the RHT enhancing behavior of graphene [21][22][23][24][25][26] may play an important role there [21]. While previous experiments reported RHT enhancements due to phonon polaritons [4][5][6], to date no experiments have reported the effect of plasmons or ultra thin films on NF RHT, this is the aim of the present work.…”
Section: *Corresponding Authors; Petervanzwol@gmailcom Joelchevriementioning
confidence: 98%
See 2 more Smart Citations
“…Optimization of TPV efficiency in NF however is difficult due to proximity effects [20]. Thus the RHT enhancing behavior of graphene [21][22][23][24][25][26] may play an important role there [21]. While previous experiments reported RHT enhancements due to phonon polaritons [4][5][6], to date no experiments have reported the effect of plasmons or ultra thin films on NF RHT, this is the aim of the present work.…”
Section: *Corresponding Authors; Petervanzwol@gmailcom Joelchevriementioning
confidence: 98%
“…In contrast in near field (NF) surface excitations such as phonon polaritons and low frequency plasmons result in an improved spatial coherence [16] and narrow bandwidths [8], leading to an increase in energy density beyond the Planck blackbody limit [1][2][3]. For materials such as SiC and SiO 2 the surface excitations are attributed to ion-vibrations [4,5], whereas for doped silicon [11] and graphene [10,21] they are due to electronic vibrations (plasmons). For these materials, the plasmon frequency can be tuned by changing the amount of free carriers.…”
Section: *Corresponding Authors; Petervanzwol@gmailcom Joelchevriementioning
confidence: 99%
See 1 more Smart Citation
“…if f f i i (13) Now the torque can be defined as the change of the molecular AM multiplied by the transition rate (1)…”
Section: Acs Nanomentioning
confidence: 99%
“…By covering graphene on doped silicon nanowires, which exhibit strong hyperbolic behaviors, Liu et al [31] theoretically demonstrated near-unity photon tunneling probability in a broad frequency range and k space by the coupling between graphene plasmon and hyperbolic modes. In terms of near-field radiative transport between dissimilar materials, Ilic et al [32] applied graphene on an emitter and showed that the near-field TPV system performance can be optimized by matching the graphene plasmon with the cell bandgap. Messina and Ben-Abdallah theoretically demonstrated improved near-field TPV efficiency between a hexagonal boron nitride (hBN) emitter and graphene-coated InSb cell by effective near-field coupling of hBN phonon modes with graphene plasmon [33].…”
Section: Introductionmentioning
confidence: 99%